Nutritional and anthropometric analysis of edentulous patients wearing implant overdentures or conventional dentures - Muller,Katia (2008)
As masticatory efficiency diminishes drastically in edentulous patients, several researchers have studied over the past two decades how dietary intake varies when different types of oral rehabilitation are provided. Since the use of implants to support prostheses in edentulous mandibles has been shown to significantly improve masticatory performance, the question remains as to whether this improvement will influence the nutritional status. The purose of this study was to evaluate the nutritional status of edentulous patients who randomly received either a mandibular conventional denture (CD) or an implant-supported overdenture (IP) 1 year previously. Weight, height, body composition and handgrip strength measurements were collected for analysis. Blood tests were performed to measure plasma parameters of diet intake. Participants responded to a Food Frequency Questionnaire and a Masticatory Function Questionnaire. Fifty-three people participated (58% men, 42% women; mean age = 53). Body composition indicators as well as plasma parameters were generally within normal range, and no statistically significant difference (p>0.05) was found between the groups. Patients in the CD group had significantly lower ratings for items regarding difficulty in chewing (p<0.05), but no significant difference was found for dietary intake (p>0.05). Although the CD wearers reported having more difficulty in chewing hard foods, both groups appeared to have a similar nutritional status.